Stylization levels of industrial design objects; Journal of Physics: Conference Series; Vol. 803 : Information Technologies in Business and Industry (ITBI2016) - Kukhta M. S. Maria Sergeevna; Sokolov A. P. Aleksandr Petrovich; Krauinsh D. P. Dmitry Petrovich; Bouchard C. (2017, 2017)
Title screen